The influence of storing mineral wool on its thermal conductivity in an open space - Noszczyk Paweł; Schabowicz Krzysztof; Tunkiewicz Maria (Open Engineering)
In engineering practice, a common problem is the lack of space on the construction site for the proper storage of building materials. The consequence of this is that building materials are stored in open spaces, where they are exposed to external atmospheric factors. This study analyses the effect of storing mineral wool for 18 months under the external conditions of moderate climate occurring in Poland on its thermal conductivity. Thirty-five samples were non-destructively tested in terms of maintaining the thermal conductivity coefficient declared by the manufacturer. The tests were performed for material with a thickness of 50 and 80 mm, and the effect of wrapping pallets in foils in maintaining thermal conductivity was also examined. The thermal conductivity coefficient was measured in standard non-destructive tests using the FOX314 plate apparatus. Despite the impact of the external environment on the mineral wool for a period of 18 months, the tests confirmed that there was no significant effect of atmospheric conditions on the thermal conductivity coefficient. The measured parameter was within the limit values specified by the manufacturer and included in the technical data sheets of the products.